Tuzla Balık Gölü kirletici kaynaklarının araştırılması - Ateş, İlker (Gebze Yüksek Teknoloji Enstitüsü, Lisansüstü Eğitim Enstitüsü, 1998)
Üçüncü Bölümde; araştırmanın ana konusu olan mağazacılık ve yüzyüze satış teknikleri ile bunların birbirleriyle ilişkisi açıklnmaya çalışılmıştır. Dördüncü Bölümde; zor müşteri diye tabir edilen müşterilerin kimler olduğu ve bu müşterilerin nasıl sadık müşteriler haline getirilebileceği, müşteri şikayetlerinin önemi ve şikayetlerin çözümlenmeleri üzerinde durulmuştur. Beşinci Bölüm; Gebze Yeni Karamürsel Mağazasında Yüzyüze Satış Tekniklerinin uygulanıp uygulanmadığı, şayet uygulanıyorsa ne kadar etkinlikle uygulandığının ölçümünü amaçlayarak YKM müşterilerine uyguladığımız anket ve bu anket sonuçlarının değerlendirmesini içeren uygulamadan oluşmaktadır.

During ancient times, bartering for goods, that people produced themselves, was the only sales technique. This changed as production methods and systems developed with the changing times. With the passage of time, production capacity began to surpass consumer demands. Thus, the abbility to sell more than the competition and to establish a firm competitive edge made a strong background in education and training a must. In this manner, sales became an actual profession. As a direct result, firms had to educate and train their sales personnel in order to increase their sales margins, and establish professional sales organizations making marketing and sales a profession. In today's world, marketing and sales does not mean an attempt at making a sale by empty promises, brilliant sounding sales pitches, and lies. A coveted salesperson is one who understands consumer motivation and psychology and knows how to make a strong sales picth. He must also know and understand the reasons behind consumer resistance to sales and the ways to break through them and be the one in control of time, and many more such technical particulars, and must be able to apply of these techniques effectively. When we consider its applications, a sale takes on two different forms:. a sale which is realized without being tied down to a certain sales base, but by going directly to the consumer.. a sale which is realized at a store or a shop This thesis is composed of four main sections and a final section.. In Section I, an attempt is made to examine the relationship between a sales program and sales techniques which include a broader definition of marjeting and its main components and In section II, the main features of marketing and sales, sales process, the advantages of sales, and personal sales is discussed.
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Çevre Mühendisliği; Environmental Engineering